Innovation and consumer protection: the case of mobile payments - Ezechukwu, Nwanneka Victoria (2018)
The ubiquitous nature of mobile devices coupled with a promise of speed and convenience makes mobile payments an attractive innovation. However, mobile payments also raise concerns with regards to consumer protection. This thesis evaluates how selected jurisdictions address these concerns. The discussion is premised on the argument that mobile payments may prove counter-productive if there are no clear regulatory rules protecting the end users. This is particularly significant for jurisdictions hoping to exploit this service to address financial exclusion problems. The thesis adopts a typology of consumer policy tools which could be used to address the identified consumer concerns. This typology guides the enquiry into how the selected jurisdictions address the consumer issues in m-payments. The purpose of this enquiry is to identify what best practices Nigerian authorities can emulate from the regulatory approach in other jurisdictions. Building on the findings of the enquiry, the thesis puts forward certain recommendations which are intended to address the shortcomings observed in the Nigerian regime.